An Examination of Refressive Da'wah in Khaled Aboe El-Fadl's Perspective on the Implementation of Qanun Syariah in Aceh - susanti-hasibuan; nanang arianto; Datuk Imam Marzuki; desiana (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The implementation of Qanun Syariah in Aceh is considered something of a dilemma. On the one hand, the implementation of the Qanun is considered to violate the provisions of Indonesian positive law, on the other hand, in the process of implementing the Qanun, the Al-Quran and Hadith are used as a basis, and it contains repressive da'wah, da'wah by making the government the perpetrator of structural da'wah, which can pressure the public to obey the teachings. Islam. This research uses a qualitative method which is research that focuses on activities, relationships, situations and conditions in the field. In carrying out this research, the author went directly to institutions related to the implementation of Qanun Islamic Sharia in Aceh, such as: Wilayatul Hisbah, Islamic Sharia, Governor, DPRA, MPU, Ministry of Law and Human Rights. The results of this research state that Qanun Syariah according to Khaled Abou el Fadl is a contemporary form of da'wah that is included in government structures. Banda Aceh has the authority to carry it out in accordance with the legitimacy of the State.